A new beginning? A bibliometric analysis of L2 vocabulary research in 1985 - Meara, Paul (LingBaW. Linguistics Beyond and Within, 2017)
This paper uses a co-citation analysis to examine the research on L2 vocabulary acquisition that was published in 1985. This year seems to mark a kind of transition in the field. Unlike the earlier years analysed in this series of papers, 1985 shows signs of a coherent L2 vocabulary research front developing. The number of papers that qualify for inclusion is much greater than in previous years, and the analysis suggests that recognisable research themes are beginning to be clearly articulated.